Some aspects of synthesis of new 2-((5-furan-2-yl, 2-metylfuran-3-yl)-4-amino-1,2,4-triazole-3-ylthio)acetic acid esters - D. M. Danilchenko (Zaporozhye State Medical University, 2016)
Introduction. The contemporary pharmaceutical industry requires implementation of new highly efficient domestic medicines. Scientists of our University has taken the first steps in this direction and registered a number of original drugs. It is impossible not to note that the active substance of these drugs has the core of 1,2,4-triazole. That is why the prospect of finding new biologically active compounds among derivatives of 1,2,4-triazole has no doubt. The aim of our work was the synthesis of new 2-((5-furan-2-yl, 2-metylfuran-3-yl)-4-amino-1,2,4-triazole-3-yltio)acetic acid esters and the study of their physical and chemical properties. Materials and methods. The study of physical and chemical properties of the obtained compounds was carried out according to methods that are listed in the State Pharmacopoeia of Ukraine. The melting point was determined on an automatic device for determining the melting point. The elemental composition of the new compounds was found on elemental analyzer. These data correspond to calculated elemental analysis. Results and discussion. The structure of synthesized substances was set using holistic method to physical and chemical analysis. The results of elemental and spectral analysis has confirmed the molecular structure of the synthesized 2-((5-furan-2-yl, 2-metylfuran-3-yl)-4-amino-1,2,4-triazole-3-ylthio)acetic acid esters, and their individuality was proven chromatographically. In addition, using the method of counter synthesis we have received a number of 2-((5-furan-2-yl, 2-metylfuran-3-yl)-4-amino-1,2,4-triazole-3-ylthio)acetic acid esters which did not give melting point depression, that also confirms the compounds' structure. Conclusions. As the results of experiment we have received 11 new compounds. The structure of the synthesized compounds has been confirmed by the complex physical and chemical methods of analysis (elemental analysis, NMR spectroscopy); in some cases counter synthesis has been applied. Individuality of derived compounds has been proved chromatographically.